In vitro technology and ADMET research in traditional Chinese medicine - Xue, Jinhao; Gao, Shiwen; You, Zhibo; Xu, Shuo; Zhou, Jiang; Jiang, Hai; Yang, Liu (Frontiers in Pharmacology, 2025)
Traditional Chinese medicine (TCM) faces many challenges in the study of absorption, distribution, metabolism, excretion and toxicity (ADME/T) because of its complexity and diversity. In vitro models, which can effectively simulate the in vivo environment and provide a platform for the analysis of the efficacy and toxicity mechanism of TCMs, play important roles in the study of TCM compounds. This paper evaluates the advantages and limitations of in vitro models (including cell models, noncell traditional models, OoC and organoid technology) from the perspective of ADMET. We emphasize the innovative application of these models in analysing the absorption kinetics, brain targeting, complex metabolic pathways, excretion characteristics and potential toxicity of TCM components. This review emphasizes the advantages of in vitro methods in meeting the challenges of TCM multicomponent analysis, including the ability to study component interactions and screen potential drug candidates. In addition, we carried out a special in-depth analysis of OoC and organoid technology and systematically explored their unique advantages in the field of traditional Chinese medicine. Moreover, combined with bibliometric analysis, the literature on the Chinese medicine ADMET published in vitro in recent years was statistically summarized, and the hot spots and trends of TCM in this research were analysed.